Preventing and treating childhood obesity by sleeping better: a systematic review - Porri, Debora; Luppino, Giovanni; Aversa, Tommaso; Corica, Domenico; Valenzise, Mariella; Messina, Maria Francesca; Pepe, Giorgia; Morabito, Letteria Anna; La Rosa, Elisa; Lugarà, Cecilia; Abbate, Tiziana; Coco, Roberto; et al. (Frontiers in Endocrinology, 2024)
Background: Childhood obesity represents a major public health issue worldwide. Evidence showed the need to implement prevention strategies mainly focused on lifestyle habits. Sleep hygiene is a variable of great interest and this review systematically examined the effects of sleep duration in increasing childhood obesity risk Methods: A systematic literature review was conducted from December 2023 to February 2024. Study selection and data extraction procedures were performed in accordance with Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Guidelines and Statement, and risk of publication bias was assessed by the Effective Public Health Practice Project Quality Assessment Tool for Quantitative Studies.Results: Original works in English were eligible for review and eleven studies that met the inclusion criteria were included. Studies collected were heterogeneous in terms of duration, sample characteristics, hours of sleep manipulation, anthropometric and hematological parameters collected, therefore it was not possible to perform a meta-analysis. A narrative synthesis of the reported evidence highlighted the impact of sleep duration above all on food intake, eating habits and hormone levels and consequently on the risk of childhood obesity development.This finding suggests the need to consider sleep hygiene as a modifiable lifestyle habit like diet and physical activity, in order to early prevent childhood obesity. Poor sleep hygiene can significantly contribute to weight gain and exacerbation of metabolic disorders linked to childhood obesity. Although more rigorous studies are needed, clinicians need to be aware of the role of sleep hygiene in reducing childhood obesity risk. details.